2018
DOI: 10.1080/15384101.2018.1442621
|View full text |Cite
|
Sign up to set email alerts
|

Inducible CRISPR genome editing platform in naive human embryonic stem cells reveals JARID2 function in self-renewal

Abstract: To easily edit the genome of naïve human embryonic stem cells (hESC), we introduced a dual cassette encoding an inducible Cas9 into the AAVS1 site of naïve hESC (iCas9). The iCas9 line retained karyotypic stability, expression of pluripotency markers, differentiation potential, and stability in 5iLA and EPS pluripotency conditions. The iCas9 line induced efficient homology-directed repair (HDR) and non-homologous end joining (NHEJ) based mutations through CRISPR-Cas9 system. We utilized the iCas9 line to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Naïve hESC Elf-1 (NIH_hESC Registry #0156, [42]) and primed human iPSC (WTC-11) [87] were cultured as previously described [26,27,43,44]. Naïve cells were grown on a feeder layer of irradiated primary mouse embryonic fibroblasts (MEF) in naïve hESC 2iL-I-F media: DMEM/F-12 media supplemented with 20% knock-out serum replacer (KSR), 0.1 mM nonessential amino acids (NEAA), 1 mM sodium pyruvate, penicillin/streptomycin (all from Invitrogen, Carlsbad, CA, USA), 0.1 mM β-mercaptoethanol (Sigma-Aldrich, St. Louis, MO, USA), 1 µM GSK3 inhibitor (CHIR99021, Selleckchem, Houston, TX, USA), 1 µM of MEK inhibitor (PD0325901, Selleckchem), 10 ng/mL human LIF (Chemicon, Temecula, CA, USA), 5 ng/mL IGF1 (Peprotech, Rocky Hill, NJ, USA) and 10 ng/mL bFGF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve hESC Elf-1 (NIH_hESC Registry #0156, [42]) and primed human iPSC (WTC-11) [87] were cultured as previously described [26,27,43,44]. Naïve cells were grown on a feeder layer of irradiated primary mouse embryonic fibroblasts (MEF) in naïve hESC 2iL-I-F media: DMEM/F-12 media supplemented with 20% knock-out serum replacer (KSR), 0.1 mM nonessential amino acids (NEAA), 1 mM sodium pyruvate, penicillin/streptomycin (all from Invitrogen, Carlsbad, CA, USA), 0.1 mM β-mercaptoethanol (Sigma-Aldrich, St. Louis, MO, USA), 1 µM GSK3 inhibitor (CHIR99021, Selleckchem, Houston, TX, USA), 1 µM of MEK inhibitor (PD0325901, Selleckchem), 10 ng/mL human LIF (Chemicon, Temecula, CA, USA), 5 ng/mL IGF1 (Peprotech, Rocky Hill, NJ, USA) and 10 ng/mL bFGF.…”
Section: Methodsmentioning
confidence: 99%
“…However, low concentration of the HDAC inhibitor sodium butyrate, which induces primed hESC to de-differentiate to an earlier stage in development [41], increases expression of miR-302 cluster while decreasing expression of miR-372 cluster [22], suggesting common microRNAs are involved in mouse and human naïve-to-primed transition. In this paper we compared naïve hESC grown in 2iLIF media [26,27,42,43,44] with primed H1 for their microRNA profile and analyzed it in parallel with their transcriptomic and metabolomic profiles. In addition, we combined existing datasets in mouse pluripotent cells [38,39,40] in order to find microRNAs regulating important pathways during the naïve to primed transition, and in naïve and primed states.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can reduce animal model usage and save time and money, while also improving quality control with respect to reproducibility and stability. A series of CRISPR-Cas9 system experiments demonstrated the role of the jumonji and AT-rich interaction domain-containing 2 genes in self-renewal in hESCs [182]. The CRISPR/Cas9 system was shown to enable scarless introduction or correction of disease-associated variants in hPSCs, thereby combining genome editing and stem cell technologies to construct genotypic "disease-in-a-dish" models [183,184].…”
Section: Maintenance and Modification Of Pluripotency And Genomic Stamentioning
confidence: 99%
“…dOTS was at least as effective in U2OS cells and the Elf1 naïve embryonic stem cell line as in HEK-293T cells ( Fig. 1d, e, S4) 27 . Finally, we found that dRNA-mediated suppression of off-target editing was durable, with dRNAs effectively decreasing off-target editing for at least 72 hours posttransfection ( Fig.…”
Section: Dead Rna Off-target Suppression (Dots) Increases On-target Smentioning
confidence: 80%